2017
DOI: 10.1002/jsfa.8257
|View full text |Cite
|
Sign up to set email alerts
|

Rennet‐induced coagulation of raw and heated camel and cow milk gels determined by instrumental techniques: effects of added calcium and phosphate

Abstract: The front-face fluorescence spectroscopy method coupled with multi-variate statistical analyses showed a high capacity for studying changes in the micelle structure throughout the rennet-induced coagulation process. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…The authors suggested that fluorescence at 466 nm can be used to determine the gelation time of rennet-induced coagulation in milk. Karoui & Kamal (2017) studied the potential of fluorescence spectroscopy to monitor rennet-induced coagulation of raw and preheated (5°C and 70°C) camels' and cows' milk at different mineral levels (calcium and phosphate). They concluded that front-face fluorescence spectroscopy was a potential technique to investigate the changes in casein micelle structure, aggregation of particles and interactions between casein and water during rennet-induced coagulation processes.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that fluorescence at 466 nm can be used to determine the gelation time of rennet-induced coagulation in milk. Karoui & Kamal (2017) studied the potential of fluorescence spectroscopy to monitor rennet-induced coagulation of raw and preheated (5°C and 70°C) camels' and cows' milk at different mineral levels (calcium and phosphate). They concluded that front-face fluorescence spectroscopy was a potential technique to investigate the changes in casein micelle structure, aggregation of particles and interactions between casein and water during rennet-induced coagulation processes.…”
Section: Introductionmentioning
confidence: 99%